Non-Glutamatergic Clozapine Augmentation Strategies: A Review and Meta-Analysis - Veerman, S. R. T.; Schulte, P. F. J.; Begemann, M. J. H.; de Haan, L. (Pharmacopsychiatry, 2014)
Persistent negative symptoms and cognitive impairment are major clinical problems in the treatment of schizophrenia. There is no convincing evidence regarding the efficacy of augmentation of clozapine with a second antipsychotic, ethyl eicosapentaenoic acid (E-EPA), an antidepressant, a mood stabilizer or extract of Ginkgo biloba in clozapine-resistant schizophrenia. We present an overview of studies in which the potential clinical utility of the addition of non-glutamatergic agents to clozapine is assessed. We performed a meta-analysis on the efficacy of both risperidone and aripiprazole compared to placebo. We compared the effects of the addition of a second antipsychotic or an antidepressant to clozapine on positive, negative, overall and affective symptoms of schizophrenia in double-blind placebo-controlled trials.
Keywords: schizophrenia; refractory; augmentation; clozapine